2018
DOI: 10.3390/ijms19082346
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Silver-Mediated DNA from Molecular Dynamics and Time Dependent Density Functional Theory

Abstract: We report a combined quantum mechanics/molecular mechanics (QM/MM) molecular dynamics and time-dependent density functional (TDDFT) study of metal-mediated deoxyribonucleic acid (M-DNA) nanostructures. For the Ag+-mediated guanine tetramer, we found the maug-cc-pvdz basis set to be sufficient for calculating electronic circular dichroism (ECD) spectra. Our calculations further show that the B3LYP, CAM-B3LYP, B3LYP*, and PBE exchange-correlation functionals are all able to predict negative peaks in the measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…We have recently profitably applied FrDEx to the study of the spectral properties of guanine-rich sequences folding in quadruple helices (G-Quadruplex, GQ). , The present study will thus also provide the opportunity to set a suitable strategy for using this approach to compute the ECD signature of B-DNA, a classical test case for many computational approaches (see, for example, and references therein). FrD-LVC has instead recently been used to study the competition between intrachromophore internal conversions (e.g., ππ* → n π*) and interchromophore excitonic and charge transfer (CT) dynamics in the Watson–Crick GC and AT base pairs. , The possible occurrence of CT and Proton Coupled Electron transfer (PCET) processes in oligonucleotides has been the focus of very intense research activity in the last years, as shown, just to cite some of the contributions, by refs .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently profitably applied FrDEx to the study of the spectral properties of guanine-rich sequences folding in quadruple helices (G-Quadruplex, GQ). , The present study will thus also provide the opportunity to set a suitable strategy for using this approach to compute the ECD signature of B-DNA, a classical test case for many computational approaches (see, for example, and references therein). FrD-LVC has instead recently been used to study the competition between intrachromophore internal conversions (e.g., ππ* → n π*) and interchromophore excitonic and charge transfer (CT) dynamics in the Watson–Crick GC and AT base pairs. , The possible occurrence of CT and Proton Coupled Electron transfer (PCET) processes in oligonucleotides has been the focus of very intense research activity in the last years, as shown, just to cite some of the contributions, by refs .…”
Section: Introductionmentioning
confidence: 99%
“…First, we use a benchmark molecule (R)-methyloxirane to validate that our RT-TDDFT implementation can produce the same ECD spectra as the LR-TDDFT implementation in both LCAO and the real-space grid mode. Then, we use a chiral Ag 4 string and a Ag +mediated guanine duplex G 2 − Ag 2+ 2 − G 2 structure 16,50 to demonstrate that LCAO RT-TDDFT adequately reproduces the rotatory strength of the reference grid mode calculated up to 8 eV. Finally, we apply the LCAO RT-TDDFT approach to a hybrid silver cluster [Ag 78 (S-BDPP) 6 (SR) 42 ] (hereafter denoted as Ag 78 ), where BDPP = 2,4-bis-(diphenylphosphino)pentane and SR = SPhCF 3 .…”
Section: Resultsmentioning
confidence: 99%
“…24 In addition, proper taking into account of the solvent environment is mandatory as well. 25 Currently, significant progress has been made in understanding of the structure and charge distributions in individual DNA-stabilized silver clusters employing force-field molecular dynamics simulations, 26,27 as well as coupled quantummechanical/molecular-mechanical (QM/MM) methods, 22,28 and density functional theory (DFT). 23,24,[29][30][31] In contrast, the collective properties of DNA-stabilized silver cluster assemblies, although experimentally proven, 16 still remain undeservedly beyond the scope of the up-to-date theoretical research.…”
mentioning
confidence: 99%
“…In addition, proper taking into account of the solvent environment is mandatory as well . Currently, significant progress has been made in understanding the structure and charge distributions in individual DNA-stabilized silver clusters employing force-field molecular dynamics simulations, , coupled quantum-mechanical/molecular-mechanical (QM/MM) methods, , and density functional theory (DFT). ,, In contrast, the collective properties of DNA-stabilized silver cluster assemblies, although experimentally proven, still remain undeservedly beyond the scope of the up-to-date theoretical research. However, such aggregates could provide unique possibility of constructing nanosized optoelectronic devices based on spatially organized arrays of noble-metal clusters serving, for instance, as ultrasmall energy and charge transmission lines. Therefore, an efficient theoretical method for a realistic description of exciton and charge propagation in such systems under the action of an external driving electric field is highly desired.…”
mentioning
confidence: 99%